2007
DOI: 10.7211/jjsrt.32.404
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of windbreaks using GIS in Otofuke, Hokkaido

Abstract: This research was done to slow the decrease in the use of windbreaks by preparing windbreaks database showing their effectiveness in preventing wind damage in Otofuke, Tokachi region in Hokkaido, the northernmost prefecture in Japan. The main research method was using the windbreak data within the GIS (geographic information system). It was shown that the total length of windbreaks in Otofuke increased from 242.3 km in 1995 to 255.0 km in 2003, which was a 12.7 km increase in 8 years. It was shown that the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Akama et al (2007) posted a photograph of either a Sakhalin fir or Sakhalin spruce arable land windbreak and gave the following caption: "Conifers which are effective for Tokachi wind in spring." In contrast to the reports of Torita et al (2003), Tsuji et al (2005Tsuji et al ( , 2007, and Akama et al (2007), it was reported that snow banks of similar sizes formed leeward to deciduous Japanese larch and evergreen Sakhalin fir arable land windbreaks in winter, suggesting that the wind velocity reduction effects of these two types of windbreak are similar (Ohshima et al, 2003;Hokkaido Forestry Research Institute, 2005). Thus, it is necessary to resolve this contradiction.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Akama et al (2007) posted a photograph of either a Sakhalin fir or Sakhalin spruce arable land windbreak and gave the following caption: "Conifers which are effective for Tokachi wind in spring." In contrast to the reports of Torita et al (2003), Tsuji et al (2005Tsuji et al ( , 2007, and Akama et al (2007), it was reported that snow banks of similar sizes formed leeward to deciduous Japanese larch and evergreen Sakhalin fir arable land windbreaks in winter, suggesting that the wind velocity reduction effects of these two types of windbreak are similar (Ohshima et al, 2003;Hokkaido Forestry Research Institute, 2005). Thus, it is necessary to resolve this contradiction.…”
Section: Introductionmentioning
confidence: 78%
“…They surveyed wind damage to red beans, but the Tokachi spring wind blew on June 9 and 10 in the year they surveyed, so leaves on the short shoots of larches were supposed to have been fully extended by then (Ohshima et al, 2002;Hirokawa and Suzuki, 2006). Tsuji et al (2007) analyzed the relationship between the densities of arable land windbreaks and the rate of wind damage and showed that the relationship was statistically non-significant. They did not state the names of the crops being investigated, nor the date when wind damage occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations